Enhancing the learning of sports skills through verbal feedback - Niźnikowski, Tomasz; Arnista, Paweł; Sadowski, Jerzy; Mastalerz, Andrzej; Romero-Ramos, Óscar; Fernández-Rodríguez, Emilio; Łuba-Arnista, Weronika; Biegajło, Michal; Różański, Pawel; Niźnikowska, Ewelina; Karaś, Andrzej; Kuśmierczyk, Piotr; et al. (Frontiers, 2025)
A critical aspect of motor skill acquisition is the feedback provided to the learner. Numerous studies have attempted to identify the most effective approach to providing feedback to individuals in the process of learning or refining motor skills. We investigated to determine the effectiveness of verbal feedback in learning the round-off back somersault on the balance beam with stable landing. Results: Based on research, itwas established that key elements could be identified in the preparatory, main and final phases. Mixed ANOVA showed that significant differences (p < 0.05) were noted due to the teaching method used (Group x Time factor) when performing the gymnastic routine of round-off back somersault with stable landing on the balance beam. Based on the Welch t test for independent data it was revealed that the group with feedback on the key elements obtained.
Methods: The research material consisted of female gymnasts (n = 16). They were randomly assigned to one of two groups: FKE group (n = 8) with feedback on key elements, or FAE group (n = 8) with 100% feedback on all errors made in the phase structure of the task. Discussion: Coaches should strategically provide feedback on key errors to optimize training and potentially improve competition performance. The study concludes that the effectiveness of learning the round-off back somersault on the beam is enhanced by purposeful verbal feedback. Reducing the frequency of feedback and focusing on key elements rather than addressing all errors proves more beneficial. Further research is needed to study the role of feedback directed at key elements in learning complex routine with multiple degrees of freedom among elite athletes in practical settings.
Keywords: Aprendizaje motor; Artistic gymnastics; Round-off back somersault; Key elements; Verbal feedback; Female gymnasts